A success story of clinical debriefings: lessons learned to promote impact and sustainability - Paquay, Méryl; Simon, Robert; Ancion, Aurore; Graas, Gwennaëlle; Ghuysen, Alexandre (Frontiers in Public Health, 2023)
The COVID-19 crisis impacted emergency departments (ED) unexpectedly and exposed teams to major issues within a constantly changing environment. We implemented post-shift clinical debriefings (CDs) from the beginning of the crisis to cope with adaptability needs. As the crisis diminished, clinicians voiced a desire to maintain the post-shift CD program, but it had to be reshaped to succeed over the long term. A strategic committee, which included physician and nurse leadership and engaged front-line staff, designed and oversaw the implementation of CD. The CD structure was brief and followed a debriefing with a good judgment format. The aim of our program was to discover and integrate an organizational learning strategy to promote patient safety, clinicians' wellbeing, and engagement with the post-shift CD as the centerpiece. In this article, we describe how post-shift CD process was performed, lessons learned from its integration into our ED strategy to ensure value and sustainability and suggestions for adapting this process at other institutions. This novel application of debriefing was well received by staff and resulted in discovering multiple areas for improvement ranging from staff interpersonal interactions and team building to hospital wider quality improvement initiatives such as patient throughput.